Oxaliplatin-related thrombocytopenia - Jardim, D. L. (2012)
Oxaliplatin is a third generation platinum compound that inhibits DNA synthesis, mainly through intrastrandal cross-links in DNA. Most of the experience with the clinical use of this drug is derived from colorectal cancer but it is also used in other tumor types such as ovary, breast, liver and non-Hodgkin's lymphoma. Thrombocytopenia is a frequent toxicity seen during oxaliplatin treatment, occurring at any grade in up to 70 % of patients and leading to delays or even discontinuation of the chemotherapy. Although myelossupression is recognized as the main cause of oxaliplatin-related thrombocytopenia, new mechanisms for this side-effect have emerged, including splenic sequestration of platelets related to oxaliplatin-induced liver damage and immune thrombocytopenia. These new pathophysiology pathways have different clinical presentations and evolution and may need specific therapeutic maneuvers. This article attempts to review this topic and provides useful clinical information for the management of oxaliplatin-related thrombocytopenia.